2001
DOI: 10.1210/endo.142.12.8556
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen-Deficient Mice Exhibit Impairment of Diet-Induced Weight Gain with Alteration in Adipose Tissue Development and Increased Locomotor Activity

Abstract: White adipose tissue is known to contain the components of the renin-angiotensin system, which gives rise to angiotensin II from angiotensinogen (AGT). Recent evidence obtained in vitro and ex vivo is in favor of angiotensin II acting as a trophic factor of adipose tissue development. To determine whether AGT plays a role in vivo in this process, comparative studies were performed in AGT-deficient (agt(-/-)) mice and control wild-type mice. The results showed that agt(-/-) mice gain less weight than wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 23 publications
8
100
2
2
Order By: Relevance
“…On the other hand, by treating mice with benazepril hydrochloride, another ACEi, Yamamoto et al [23] have observed an improved locomotor activity in the animals. Using a genetic approach to determine whether angiotensinogen acts as a trophic factor of adipose tissue development, Massiera et al [24] analyzed the phenotype of angiotensinogen knockout mice. The results showed that those mice gain less weight than wildtype mice in response to a regular chow or high fat diet, with specific alteration of adipose tissue mass.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, by treating mice with benazepril hydrochloride, another ACEi, Yamamoto et al [23] have observed an improved locomotor activity in the animals. Using a genetic approach to determine whether angiotensinogen acts as a trophic factor of adipose tissue development, Massiera et al [24] analyzed the phenotype of angiotensinogen knockout mice. The results showed that those mice gain less weight than wildtype mice in response to a regular chow or high fat diet, with specific alteration of adipose tissue mass.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological blockade or genetic deletion of any component of the RAS in rodent models results in significant changes in body weight, body composition, food intake, digestive efficiency, physical activity, and/or metabolic rate [10][11][12][13][14][15][16][17][18], while transgenic expression of renin in rats results in obesity [19]. It is surprising to find, then, that the beneficial metabolic effects of modulating the RAS are largely unimpressive in human subjects [59-61, 62•, 63, 64].…”
Section: The Brain Ras In Energy Balancementioning
confidence: 99%
“…Nonetheless, the relationship between circulating RAS activity and obesity is likely bi-directional. The RAS contributes to energy balance, as genetic [10][11][12][13] and pharmacological [14][15][16][17][18] inhibition of the RAS in rodent models generally results in a negative energy balance (lean animals and/or resistance to weight gain), and chronic elevations in plasma renin activity can lead to obesity [19].…”
Section: Introduction the Ras And Obesitymentioning
confidence: 99%
“…Among the local effects, angiotensin II is thought to act as a growth factor for fat cells. Systemically, researchers have expressed the AGT gene in adipose tissue of AGT-knockout mice, creating a transgenic-knockout mouse model in which production of AGT is limited to adipose tissue [72]. In these animals, systemic levels of AGT increased to 10% of wild-type levels, demonstrating that AGT produced in fat cells can enter the circulation.…”
Section: Abnormal Divalent Cation Metabolism and Vascular Insulin/insmentioning
confidence: 99%